Depresión Posparto en las pacientes del servicio de Ginecología - Hospital Básico de Cayambe - Gonza Calapaqui, Christian Javier (2025)
Postpartum depression is a mental health disorder characterized by a persistent feeling of sadness and anxiety that interferes with daily life routines. This project aimed at developing an educational plan to support the management and cope with postpartum depression in patients who attend the gynecology area in the Basic Hospital Cayambe in 2025. A quantitative methodology was applied, transversal and descriptive; non- experimental research was carried out using solid and scientific bibliographic resources to develop the theoretical framework. The study population was comprised of patients who attended the gynecology service of the Basic Hospital Cayambe, being the selected population of 45 postpartum patients. The technique used was a survey through a questionnaire related to the study research variables. Results showed that 45% of women were diagnosed previously with depression, 52% considered that postpartum depression is a condition that does not require medical treatment, 45% of the patients experienced some complications during their pregnancies, 57% had not received support from a mental health professional after childbirth and 78% of the patients considered that it is fundamental to implement educational strategies to prevent postpartum depression. Given these reasons, it can be concluded that nursing interventions are essential for their key role in detecting symptoms at early stages and represent emotional support for patients during the health recovery process.